Air Asia: Challenges In A Booming Budget Airline Industry - Sauffee Afandi, Aizan Suhaira (2004)
The new Air Asia is actually roughly modelled based on the Irish low -cost arlimes, Ryanair.This study has several key objectives, which are : To gauge the feasibility and applicability of the budget airline industry in Asia; To determine the potential competitiveness in this industry and how they may impact the players and the customers; To analyze AirAsia's potential in this increasingly competitive and potentially crowded industry; To recommend strategies that may help Air Asia maintain and increase its lead in the industry.